Obstacles to Environmental Progress A U.S. perspective - Schulze, Peter (UCL Press, 2022)
environment;policy;biology;earth sciences;United States;obstacles to progress;environmental policy;environmental law;environmental regulation;environmental science;environmental progress;environmental solutions;environmental justice;sustainability;uncertainty;decision processes;climate change;problem solving;unintended consequences;systems perspective;environmental monitoring;freedom and environmental policy;scientific uncertainty;cost-benefit analysis;flawed US democracy;disenfranchisement;gerrymandering;campaign finance;technological surprise;environmental design;trade and the environment;economic growth and the environment;statistical uncertainty;inference and extrapolation;scientific errors